2013
DOI: 10.5296/jbls.v4i2.3880
|View full text |Cite
|
Sign up to set email alerts
|

Performances of a Yard-Scale Surface Flow Wetland Vegetated with Echinochloa Crus-Pavonis in the Removal of Nutrients and Faecal Bacteria from Domestic Wastewater

Abstract: Several macrophytes are being tested in experimental wetlands systems in Cameroon, for the treatment of domestic wastewater. The aim of the present research was to assess the performances of a yard scale surface flow wetland vegetated with Echinochloa crus-pavonis, ISSN 2157-6076 2013 www.macrothink.org/jbls 252 in the removal of nutrients and faecal bacteria from primarily treated effluent. A wetland vegetated with the macrophyte and a non-vegetated wetland (control) were continuously fed with primarily trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…No significant differences were noticed in the removal of the two species in this work. These results are similar to those reported by [25].…”
Section: Some Csupporting
confidence: 83%
See 1 more Smart Citation
“…No significant differences were noticed in the removal of the two species in this work. These results are similar to those reported by [25].…”
Section: Some Csupporting
confidence: 83%
“…These potentials included biomass production in vegetated bed systems, their ability in faecal sludge dewatering improvement as well as biosolids recovery, their responses to salinity stress, the nutritional potentials as fodder after harvest from treatment beds as well as their potentials in the removal of bio-indicators of faecal contamination from wastewater [14] [17] [21] [22] [23] [24] [25]. But there has been no concern on the ability of Fuirena umbellata on biomass production in constructed wetlands, nutrients removal and in the reduction of bio-indicators of faecal contamination from wastewater, despite its presence and proliferation in natural polluted and non-polluted wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…However, some plants especially those closer to the gabions at the inlet showed a stunted growth probably due to the high concentration of wastewater at the inlet during the dry season. This linear growth in growth parameters was also observed by[14] [15] using Echinochloa crus-pavonis and Fuirena umbellata respectively.…”
supporting
confidence: 72%
“…It is observed that more biodegradation of organic matter occurred in the wetland treatment beds such that the amount of phosphate in the outflow was more than the inflow especially in the treatment bed vegetated with Brilantaisia bauchiensis followed by the bed with Polygonum salicifolium. The high growth and the linear growth of these plants in the wastewater treatment station is probably due to the availability of nutrients particularly Nitrogen and phosphorus present in the water which probably resulted from the transformations of nitrates and phosphates since these compounds were abundantly available in the wastewater but were removed more in the vegetated beds than in the control [14] [15]. It is evident that the presence of wastewater significantly increased growth of shoots and plant density in CW [15] [32].…”
Section: Shoot Production and Plants Densitymentioning
confidence: 99%
See 1 more Smart Citation